ALLAMANDA CATHARTICA LINN.: EXTRACTION AND PHARMACEUTICAL EVALUATION OF VARIOUS EXTRACTS OF LEAVES AND FLOWERS - Fartyal, Meenakshi (International Journal of Current Pharmaceutical Research, 2016)
Objective: Extraction and evaluation of the antifungal activity of extracts from leaves and flowers of Allamanda cathartica (Apocynaceae) Linn. Methods: Leaves and flowers of A. cathartica were collected, dried and extracted by using well-established methods for alkaloids, flavonoids, steroids and crude extracts in polar and non-polar solvents. Extracts were screened for antifungal activity using â€˜Disc Diffusion Assay’ against Candida albicans (Yeast), Aspergillus flavus and Tricophyton mentagrophyte (fungi). Inhibition zone (IZ), Activity index (AI), Minimum inhibitory concentration (MIC), Minimum fungicidal concentration (MFC) and Total activity (TA) were studied. Mean and standard deviation has also been calculated. Results: C. albicans found to be the most susceptible organism while T. mentagrophyte found to be resistant. Alkaloid of leaf (IZ= 22 mm, AI= 0.65Â±0.02, MIC= 0.156 mg/ml, MFC= 0.078 mg/ml, TA= 278.85 ml/g) showed the best activity against C. albicans. Pet ether extract (IZ= 12 mm, AI= 0.40Â±0.02, MIC= 0.312 mg/ml, MFC= 0.156 mg/ml, TA= 57.24 ml/g) and water extract (IZ= 13 mm, AI= 0.43Â±0.02, MIC= 0.312 mg/ml, MFC= 0.156 mg/ml, TA= 49.68 ml/g) of flower also showed very good activities against C. albicans. The range of MIC and MFC found to be 1.25-0.156 mg/ml and 0.625-0.078 mg/ml, respectively. Conclusion: Results indicate the good antifungal potency of extracts against tested microorganisms. Hence, may be explored for the formation of new antifungal drugs.